Motives for participation in physical activity among libyan adults - Elmahgoub, Sami; Mohamed, Hassan; Hmmier, Abduladim; Eltaguri, Adel (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Objectives: The study aimed to determine motives for physical activity (PA) participation in Libyan adults and compare motives related to sex and places of participation (indoor vs. outdoor). Participants and Methods: A cross-sectional questionnaire-based study was conducted. The questionnaire was adapted from the Exercise Motivation Inventory version 2. Six hundred Libyan adults (300 males and 300 females) were involved in this study. Results: In general, positive health, activation, and avoiding ill-health (4.83 ± 0.89, 4.20 ± 0.93, 4.09 ± 1.00, mean ± standard deviation [SD]) were the most common motives for PA participation, respectively, while competition, afﬁliation, health pressure, and social status (2.73 ± 1.29, 2.69 ± 1.21, 2.59 ± 1.29, 2.50 ± 1.24, mean ± SD) were the least motivational factors, respectively. In males, enjoyment, social status, afﬁliation, competition, health pressure, strength, and endurance were significantly higher (P= 0.017, 0.000, 0.010, 0.000, 0.007, 0.024). In contrast, activation, positive health, weight control, appearance, and fitness were significantly higher in females (P= 0.002, 0.001, 0.000, 0.000, 0.005). In addition, health pressure, avoiding ill-health, and positive health motives were similar in adults practicing PA indoor and outdoor. In contrast, other motives tended to be significantly higher in indoor activities. Conclusions: Motives for PA participation differ across participants' sex and places of participation among Libyan adults. It is crucial to understand the motives for PA participation to capitalize on the positive motives to increase their participation and enhance the positive effects of increased PA in the community.
Keywords: Exercise motivation inventory-2; Libya; motivation; physical activity participation